The 30-item and 15-item Boston naming test Czech version: Item response analysis and normative values for healthy older adults - Bezdicek, Ondrej; Rosická, Anna Marie; Mana, Josef; Libon, David J; Kopeček, Miloslav; Georgi, Hana (Journal of clinical and experimental neuropsychology, 2021)
OBJECTIVE: The Boston Naming Test (BNT) is the most widely used test to assess visual confrontation naming in both research and clinical settings. Recently, an abbreviated Czech version of the BNT was described. The purpose of this study is to assess the validity of this new test at the item level with advanced psychometric methods to assess its equivalence with the original test. The rationale was to help busy clinicians in the differential diagnosis of language disorders. METHOD: We administered the BNT-30 (odd item form of BNT-60) (N = 535; 75.61 ± 9.11; 60-96 years) and shortened the BNT-15 (N = 754; 71.94 ± 7.88; 60-96 years) to a large sample of healthy older adults. RESULTS: Significant but low associations between BNT performance and age, education, and sex were found. We found strong evidence for the unidimensionality of both BNT-15/BNT-30 versions in healthy adults (p's < .001). CONCLUSION: In-depth psychometric analysis of the BNT-15 and BNT-30 Czech versions show that test stimuli function in a similar fashion as the original BNT. Normative values adjusting for the influence of age, education, and sex are provided for use in clinical settings and future cross-cultural comparisons.
Keywords: Psychometrics; item difficulty/easiness; visual confrontation naming; Česká republika; jazyk (prostředek komunikace); Language Tests; normative data; item response theory; Aged; senioři; jazykové testy; Neuropsychological Tests; Czech Republic; lidé; psychometrie; Humans; picture naming; Boston naming test; construct validity; neuropsychologické testy; Language